School-Based 4-H Programming: Getting Started - Vanessa Spero Swingle; Susan Munyan (EDIS)
School-based programs provide an opportunity to youth who would not be able to participate in traditional 4-H club offerings otherwise. If you want to expand your 4-H program in diversity, subject matter, and/or number of youth reached, school-based programming may be the solution for you. This 6-page document discusses school-based programs, differences between school-based programming and traditional club programming, reasons to start school-based programs, ways to work with school sites, and enrollment for school-based program youth. It is part of the 4-H 101 Fact Sheet series. Written by Vanessa Spero-Swingle and Susan Munyan, and published by the UF/IFAS 4-H Youth Development Department, April 2018. http://edis.ifas.ufl.edu/4h389